Functional Microgels: Recent Advances in Their Biomedical Applications. Issue 39 (23rd July 2018) - Agrawal, Garima; Agrawal, Rahul
Abstract: Here, a spotlight is shown on aqueous microgel particles which exhibit a great potential for various biomedical applications such as drug delivery, cell imaging, and tissue engineering. Herein, different synthetic methods to develop microgels with desirable functionality and properties along with degradable strategies to ensure their renal clearance are briefly presented. A special focus is given on the ability of microgels to respond to various stimuli such as temperature, pH, redox potential, magnetic field, light, etc., which helps not only to adjust their physical and chemical properties, and degradability on demand, but also the release of encapsulated bioactive molecules and thus making them suitable for drug delivery. Furthermore, recent developments in using the functional microgels for cell imaging and tissue regeneration are reviewed. The results reviewed here encourage the development of a new class of microgels which are able to intelligently perform in a complex biological environment. Finally, various challenges and possibilities are discussed in order to achieve their successful clinical use in future. Abstract : Smart colloidal microgels exhibit a great potential for various biomedical applications. Herein, a critical review of different methods for designing functional microgels is provided. Additionally, different crosslinking strategies to achieve degradable microgels are highlighted. Recent advancements in the usage of functional microgels for drug delivery, cell imaging, and tissue engineering are summarized here.